A Discussion on empowering role of education on HR practitioners’ ethical conduct - Şule Aydın Turan; Onur Metin; Sevgi Dönmez Maç; Semih Okutan (Sakarya Üniversitesi İşletme Enstitüsü Dergisi)
This study aims to discuss whether HR educationcould be a source for empowering HR professionals to overcome unethicalbehaviors and ethical dilemmas.Accordingly, in the paper, first of all, the unethical behaviors andethical dilemmas that the HR professionals may encounter are outlined. Afterthat, HR education, for more humanistic workplace development, is discussedconceptually. Thirdly, the current perspective of the undergraduate’s level ofHR education and the national occupational standards prepared by the VocationalQualifications Authority regarding HR-related professions are examined in termsof mainstream and ethical/critical HR approaches. Finally, the contribution ofethical HR education for a more balanced perspective on working life isdiscussed. Content analysis is used for the evaluation of the curriculum of theHR departments in higher education institutions, and the occupationalstandards. The findings of the studyreveal that both the private sector’s expectations and HR education are highlyin line with the mainstream perspective of HR. The findings are significant interms of showing that the HR practitioners at present have a dominantlyunitarist perspective, and their expectations from the HR-related occupations’practitioners have clearly managerialist and unitarist tendencies. Theorientations of higher education programs, on the other hand, are in the samedirection to a large extent. In the context of the findings, in conclusion, itis suggested that the HR education for a more humanistic and balanced workinglife, even if in the long-term, may be redesigned in an ethically andcritically strengthened, and strategically and morally balanced manner.